Dimensional changes of hard and soft tissues in post-extraction sites: evaluation of two biomaterials - Maria Catalina Castaño-Granada; Natalia Roldán-Tamayo; Jorge Alberto Arismendi-Echavarría; Sandra Cristina Calle-Muñoz (Universidad de Antioquia, 2016)
Introduction: the techniques for alveolar ridge preservation with different biomaterials show better healing processes than those treatments which do not carry out procedures nor modify the patterns of alveolar bone resorption. The goal of this study was to evaluate the clinical, radiographic, and histological changes of tissues in post-extraction sites after 90 and 180 days by using two biomaterials for alveolar ridge preservation. Materials: descriptive study involving the extraction of twenty-seven uni- and biradicular teeth comparing two biomaterials randomly distributed. Group A received resorbable synthetic hydroxyapatite (OsseoU) and Group B received mineralized freeze-dried allogeneic bone (Tissue Bank®). Quantitative and qualitative measurements were made 180 days post-extraction. The statistical analysis was conducted with the Shapiro-Wilks, Levine, and Student t tests. Results: comparing the two biomaterials on day 180 yielded no statistically significant differences in terms of the "height" variable. The "width" variable yields a p = 0.010 value, suggesting statistically significant differences, since Group A is 0.789 ± 0.276 times better (3.72 ± 0.76) than group B (2.93 ± 0.55). The radiographic evaluation did not yield differences between both groups (p= 0.711). Conclusion: this study shows the dimensional changes of post-extraction sites in both groups, with a clinical difference in ridge width, and no radiographic or histological differences, neither statistically significant changes in terms of alveolar ridge height. Resorbable synthetic hydroxyapatite (OsseoU) is then a biomaterial as effective as mineralized freeze-dried allogeneic bone (Tissue Bank®).